Understanding public perception of hydraulic fracturing: a case study in Spain - Daniele Costa (2017)
Public acceptance is crucial for the implementation of energy technologies. Hydraulic fracturing is a technology widely used in the USA for natural gas production from shale formations, but currently finds strong public opposition worldwide, especially in Europe. Shale gas exploitation and exploration have the potential to significantly reduce import dependency in several countries, including Spain. To better understand public opinion on this issue, this article reports a survey targeting both the entire Spanish population and the inhabitants of the province of Burgos, the location where shale gas exploration permits have already been issued. Results demonstrate that half of the Spanish population opposes shale gas, and this opposition increases in autonomous communities that are closer to possible exploration sites. The results also show that socio-demographic aspects are not strong predictors of opposition. In addition, Burgos' population show different behaviours toward shale gas that demonstrates that proximity and prospect of shale gas development affects opinion. Finally, there is still a great level of unfamiliarity with high volume hydraulic fracturing and shale gas in both populations sampled.